Kepribadian dalam ragam budaya: Potret mahasiswa baru UIN Maulana Malik Ibrahim Malang - Najwa, Aina (Maliki Interdisciplinary Journal, 2025)
This article explores the influence of ethnic and cultural diversity on the personalities of new students at UIN Maulana Malik Ibrahim Malang. Through observations of students from various cultural backgrounds, it was found that traditions, norms, language, and value systems inherited within each culture significantly shape individuals’ ways of thinking, attitudes, and behaviors. This uniqueness presents challenges such as stereotypes and misconceptions, but also offers opportunities to enhance collaboration, tolerance, and intercultural understanding. By recognizing and respecting individual personalities shaped by culture, campus life becomes more harmonious, inclusive, and competitive. The article recommends strengthening multicultural education and intercultural dialogue as strategic steps to build an academic environment that values diversity.